Feraid (Ferheng-i vajgan-ı düşvar u nevadir-i kuran-ı kerim ber-page-i tercemeha-yı kühen = Fara'ed: A lexicon of difficult and infrequent words of Quran based on the old translation - Caferi, Ferzad. (Tahran)
762+4 s.